The Comedy of Manners from Sheridan to Maugham - Sawyer, Newell W. (University of Pennsylvania Press, 2016)
In the two centuries between the first performance of The School for Scandal by Richard Brinsley Sheridan and the outbreak of the First World War, the stage provided an accurate mirror of the changing mores of English society. "High comedy," Newell W. Sawyer writes, "views man as a social animal in the midst of his fellows, with customs, conventions, and traditions of his own devising, and prods him gently or mockingly, as he stands confounded by that which he has made." The comedy of manners became, from its prototype, a dramatic category reflecting the life, thought, and manners of upper-class society, faithful to its traditions and philosophy, and as such offers an ideal medium for such a study as Professor Sawyer has here undertaken. The result is a book that is at once entertaining and serious, a study of two centuries of the British stage,